Принципи та аналітичні засоби реконструкції структур ймовірнісних залежностей у спеціальному класі - Балабанов, О.С. (Проблеми програмування, 2017)
Запропоновано та обґрунтовано набір емпіричних резолюції, які спираються виключно на безумовні залежності двох змінних та забезпечують ідентифікацію безпосередніх зв’язків (ребер) у структурах залежностей в класі монопотокових графів. Цей клас структур є підкласом ациклонних орграфів та суперкласом для полі-лісів. Охарактеризовано властивості монопотокових моделей. Коректність розроблених емпіричних резолюцій ґрунтується на емпірично надійному припущенні безумовної (маргінальної) реберної неоманливості. Предложен и обоснован набор эмпирических резолюций, которые опираются исключительно на безусловные зависимости двух переменных и обеспечивают идентификацию непосредственных связей (ребер) в структурах зависимостей в классе монопотоковых графов. Этот класс структур является подклассом ациклонных орграфов и суперклассом для поли-лесов. Охарактеризованы свойства монопотоковых моделей. Корректность разработанных эмпирических резолюций основывается на эмпирически надежном предположении безусловной (маргинальной) реберной необманчивости. We examine a problem of reconstruction of dependency structure from data. It is assumed that model structure belongs to class of "mono-flow" graphs, which is a subclass of acyclonic digraph (known as DAGs) and is super-class relatively to the poly-trees. Properties of the mono-flow dependency models are examined, especially in terms of patterns of unconditional dependencies and mutual information. We characterize the twin-association evolving among two variables. Specialized methods of inference of mono-flow dependency model are briefly reviewed. To justify correctness of model recovery from data we formulate an assumption of unconditional (marginal) edge-wise faithfulness, perhaps the most reliable one among all simple versions of Causal faithfulness assumption. On the basis of the assumption and the properties of mono-flow dependency models we derive several empirical resolutions for edge identification, which make use 2-placed statistics only. A lot of experiments with artificial data have demonstrated efficiency of the resolutions in that they correctly recover many edges and commit low error rate.